725 Paediatric Resuscitation Burns Maintenance Fluid Selection - a Retrospective Review of Cases and Adherence to NICE, LSEBN and EMSB Guidelines. (19th August 2022) - Noton, T; Al Omran, Y; Williams, A
Abstract: Aim: Appropriate fluid management in major burn injuries is directly related to burn survival rates. Despite this fact, there are still controversies regarding the choice of replacement fluid given during the resuscitation and maintenance stages in the acute management of burns. The aims of this study are to compare current paediatric maintenance fluid prescriptions against current guidelines, and to assess whether there is of any adverse effects (i.e., electrolyte disturbance). Method: Details of all paediatric burn's patients (aged 18 years or under) who were admitted to the paediatric burns ward during an 18-month-period were screened. Only those coded as having sustained 10% TBSA burns or greater were included in data analysis. Data was then sourced using Cerner electronic patient record software. Results: A total of 17 patients were identified, all sustaining scald injuries with between 10% and 22% TBSA burns. Every patient was given 0.45% NaCl with 5% dextrose as maintenance fluid. All IV maintenance supplementation was ceased after 24hrs. Only 53% of patients had pre- and post-fluid bloods taken. Average drop in sodium amongst these patients was 2mmol, with largest drop (5mmol) in the patient with the largest burns % TBSA. Conclusions: We found zero compliance with current NICE guidelines, which suggests an isotonic crystalloid (such as 0.9% NaCl with 5% dextrose) for maintenance, therefore guidance in line with this should be considered. Larger burns TBSA or prolonged IV fluids may amplify electrolyte imbalances. The importance of consistent electrolyte monitoring amongst this patient cohort is key and should be encouraged.